Control of effective cooling rate upon magnetron sputter deposition of glassy Ge15Te85. (15th March 2020) - Pries, Julian; Wei, Shuai; Hoff, Felix; Lucas, Pierre; Wuttig, Matthias
Abstract: Reducing the enthalpy of as-deposited amorphous films is desirable as it improves their kinetic stability and enhances the reliability of resulting devices. Here we demonstrate that Ge15 Te85 glass films of lower enthalpy are produced by increasing the voltage during magnetron sputter deposition. An increase of 100 V leads to a drop in effective cooling rate of almost three orders of magnitude, thereby yielding markedly lower enthalpy glasses. The sputtering voltage therefore constitutes a novel parameter for tuning the fictive temperature of glass films, which could help to obtain ultra-stable glasses in combination with substrate temperature control. Graphical abstract: Image, graphical abstract